From the editor - Bukh, Vladimir (project baikal, 2007)
For the topic of this issue we have chosen the environment's component that remains after the grand architecture – the ground between buildings and smaller forms that fill it. It is painful that this subject turns out to be of little significance for our urbanists. The residual principle of treatment of land reclamation culture imparts disorder, hasty temporariness to our cities, as if we are not residents here. The topic's urgency has to be proven by other's experience.